Analysis of Meteorological Epidemic Factors and Soil Improvement Controlling Technology of Tobacco Bacterial Wilt （Ralstonia solanacarum） - Yang Peiwen Yang Qunhui Ni Ming Guo Yingcheng Xiao Zhixin Hu Zhiming Li Jiarui Yang Mingying (Plant Diseases and Pests(植物病虫害研究：英文版), 2017)
[Objective] The paper was to analyze the meteorological epidemic factors for occurrence and prevalence of tobacco bacterial wilt （ Ralstonia solanaca- rum）, and to study control effects of different soil conditioners on the bacterial disease in Gacligongshan demonstration area of green, ecological, high quality tobac- co leaf production. [Method] The plots attacked by tobacco bacterial wilt over the years were selected and the incidence of the disease was periodically surveyed in tobacco growth period in 2012, 2103 and 2014, respectively. 10 d Effective accumulated temperature and rainfall were counted according to the meteorological data, and the relationship between meteorological factors and disease index was analyzed. The control effects of three kinds of soil conditioners ＂Zhuanggenfeng＂, refined fulvic acid and lime on tobacco bacterial wilt were tested. [ Result] The analysis results of meteorological factors showed that 10 d effective accumulated temperature and rainfall were positively correlated to disease index. The variation curve of 10 d effective accumulated temperature and rainfall reflected the change trend of disease index. The pH values were increased by 0.57, 0.50 and 0.72 respectively after applying ＂Zhuanggenfeng＂, refined fulvic acid and lime. The aver- age control effects on tobacco bacterial wilt were 60.74% -62. 18%, 53.05% -59.53%, and 48.59% -58.53%, respectively. [ Conclusion] 10 d Effective accumulated temperature and rainfall could be used as important reference for disease forecasting and controUing. The usage of soil conditioner has a certain preven- tion and control effect on tobacco bacterial wilt disease by forming soil conditions conducive to flue-cured tobacco growth but adverse to disease survival, which is an effective auxiliary method against the disease.